Aesthetic Surgical Pathway in Permanent Facial Filler Removal - Pascali, Michele; Chirico, Fabrizio; Rugge, Luigi; Rauso, Raffaele (Facial Plastic Surgery, 2023)
Although permanent fillers have been introduced in order to get long-lasting results, many studies have shown numerous severe and disfiguring complications. Nonsurgical procedures may mitigate those adverse events but the only way to remove the filler previously injected is represented by surgical excision. We present a pathway of facial surgical accesses to be performed achieving two goals: permanent filler removal and restore facial aesthetic balance. The proposed surgical accesses are already standardized in aesthetic surgical practice in order to avoid direct excision and unpleasant facial scar. A total of 231 patients underwent surgery for permanent filler removal and aesthetic restoration of the involved facial area, represented by forehead, glabella, nose, cheeks, eyelids, chin, jawline, and lips. Magnetic resonance evaluation was performed with the exception of lip patients who were evaluated with ultrasound. Postoperative follow-up was 12 months to 6 years. Subjective and objective methods were used for outcome evaluation according to the FACE-Q questionnaire. Functional and aesthetic correction was scored using the patient-graded Global Aesthetic Improvement Scale (GAIS), overall patient satisfaction was assessed by a five-point scale questionnaire. Functional and aesthetic restoration was globally recognized as improved according to the GAIS. Patients reported high levels of satisfaction assessed by a five-point scale questionnaire. A very good satisfaction level was registered in both subjective and objective judgment scores. To the best of our knowledge, we present the largest case series regarding surgical removal of permanent facial fillers. A proper preoperative evaluation, filler removal followed by restorative facial aesthetic surgery technique is paramount to approach challenging cases.
Keywords: permanent filler; filler removal; filler complications; facial reconstruction; aesthetic surgery